Iodine-Promoted Disproportionate Coupling Reaction of Arylsulfonyl Hydrazides: A Simple and Green Access to Thiosulfonates - Chen, Qi; Chen, Zhao-Hua; Liang, Yong-Tong; Zeng, Yong; Yu, Shi-Wei; Yang, Kai; Wang, Zhao-Yang (Synthesis, 2024)
An environmentally friendly iodine-promoted disproportionate coupling reaction of arylsulfonyl hydrazides is reported. This strategy can synthesize thiosulfonates with medium to excellent yields, and features a green system, wide applicability of substrates, and easy availability of raw materials. The preliminary mechanistic study reveals that iodine plays an important role in the radical reaction process.
Keywords: disproportionate coupling reaction; arylsulfonyl hydrazide; thiosulfonate; green synthesis; iodine-promoted; radical reaction